The Effectiveness of Fiscal Decentralization in Alleviating Poverty from An Sharia Economic Perspective in Kebumen, Indonesia - Muyassarah, Muyassarah; Ghofur, Abdul; Mutadho, Ali; Mohamad, Maizatul Saadiah binti; Mansur, Mansur (Madania: Jurnal Kajian Keislaman, 2023)
The research objective is to determine the effectiveness of fiscal independence in poverty alleviation based on economic principles, efficiency, effectiveness, independence, and the pattern of regional and central relations. This research uses a qualitative approach, secondary data from the 2019-2021 APBD, and interviews by looking at the economic formula, efficiency, and effectiveness, as well as the independence of regional financial management and analysis techniques with an Islamic economic approach.Kebumen's financial management has not been able to reduce the poverty rate because of its low self-support because it still needs a budget injection from the province/central. This paper needs further research on the Central Java province poverty alleviation assistance program, accommodates a larger sample, and involves a wider range of informants and comprehensive analysis.The APBD encourages the empowerment movement independently through assistance so that the poor group becomes independent in meeting their needs without depending on others. Financial management approach input-program process-outcome-evaluation-feedback. The focus of the measurement of the APBD describes the independence of the regional budget, which is believed to eradicate poverty as a household problem in the region, the economic approach, effectiveness, efficiency, independence, and the pattern of relations with an Islamic economic approach. Penelitian ini bertujuan untuk mengetahui efektivitas kemandirian fiskal dalam pengentasan kemiskinan berdasarkan prinsip ekonomi, efisiensi, efektivitas, kemandirian, dan pola hubungan daerah dan pusat. Penelitian ini menggunakan pendekatan kualitatif, data sekunder APBD 2019-2021, dan wawancara dengan melihat rumus ekonomi, efisiensi dan efektivitas, serta kemandirian pengelolaan keuangan daerah dan teknik analisisnya dengan pendekatan ekonomi syariah. Hasil penelitian menunjukkan bahwa pengelolaan keuangan Kebumen belum mampu menurunkan angka kemiskinan karena rendahnya swasembada karena masih memerlukan suntikan anggaran dari provinsi/pusat. Penelitian ini merekomendasikan bahwa APBD hendaknya mendorong gerakan pemberdayaan secara mandiri melalui pendampingan agar kelompok miskin menjadi mandiri dalam memenuhi kebutuhannya tanpa bergantung pada orang lain. Pengelolaan keuangan menggunakan pendekatan input-program, proses-hasil-evaluasi-umpan balik. Fokus pengukuran APBD menggambarkan kemandirian APBD yang diyakini dapat mengentaskan kemiskinan sebagai permasalahan rumah tangga di daerah, pendekatan ekonomi, efektivitas, efisiensi, kemandirian, dan pola hubungan dengan pendekatan ekonomi syariah.